Biological Compatibility of Polyethylene Terephthalate Track Membranes: Growth, Proliferation, and Viability of Cells in Culture Systems - Balyasin, M.V.; Serpionov, G.V.; Krasheninnikov, M.E.; Lyundup, А.V.; Nechaev, A. N. (Karagandy University of the name of academician E.A. Buketov, 2025)
This study evaluated the biocompatibility of polyethylene terephthalate track membranes (PET TMs) obtained by heavy ion irradiation followed by chemical etching, with respect to cell growth, proliferation, and viability in culture systems. Physical parameters of the PET TMs were determined, including Young’s modulus, ultimate tensile strength, and contact angle. Cytotoxicity of PET TMs was studied on three cell cultures: the epithelial line MCF7 (adenocarcinoma), fibroblast-like mouse line 3T3, and a primary culture of mesenchymal stromal cells (MSCs) isolated from rabbit bone marrow. Cytotoxicity was assessed using two methods: extraction from the material and the direct contact method in accordance with the Interstate Standard ISO 10993-5-2011, IDT. The results demonstrated that neither PET TM extracts nor direct contact samples significantly affected cell growth. The proliferation rate of MCF7 cells was 0.01531 1/h for the extract and 0.01568 1/h for direct contact, which did not differ statistically from the control group (0.01877 1/h, p = 0.138). Microscopic analysis confirmed the preservation of cellular morphology: MCF7 cells retained cuboidal morphology, while 3T3 cells exhibited a spindle-shaped morphology. Real-time cell analysis (RTCA) revealed no significant effect of the tested samples on the cellular index (Ci), further supporting the absence of a cytotoxic effect. Visual observations of cell cultures after incubation with the studied samples also did not reveal cell confluence and morphology changes. These findings provide important evidence for the safety of PET TMs in biomedical research and cell culture systems, recommending them for further research in tissue engineering and regenerative medicine.
Keywords: heavy ion irradiation; chemical etching; track-etched membrane; polyethylene terephthalate; regenerative medicine; cytotoxicity; cell culturing; tissue engineering